Psychometric Validation of the Revised Child Anxiety and Depression Scales – Parent Version (RCADS-P) in Children Evaluated For ADHD - Becker, Stephen P. (Assessment, 2017)
Children with attention-deficit/hyperactivity disorder (ADHD) frequently experience comorbid internalizing symptoms. The Revised Child Anxiety and Depression Scales–Parent Version (RCADS-P) is a frequently-used measure of anxiety and depression in children, though its psychometric properties remain unexamined in children referred for ADHD specifically. The present study evaluated the RCADS-P in 372 children (ages 7-12; 68% male) referred for evaluation at an ADHD specialty clinic (89% met criteria for ADHD). In addition to the RCADS-P, parents completed the Vanderbilt ADHD Diagnostic Rating Scale (VADRS) and Child Behavior Checklist (CBCL) and were administered the Kiddie Schedule for Affective Disorders and Schizophrenia for School-Age Children (K-SADS) semi-structured diagnostic interview. Teacher ratings were available for approximately half of the sample. Factor structure, reliability, convergent/discriminant validity, and sensitivity/specificity were examined. Results supported the six-factor structure of the RCADS-P. The RCADS-P demonstrated adequate internal consistency as well as convergent and discriminant validity with other parent ratings and, to a somewhat lesser extent, teacher ratings. Children with an internalizing diagnosis had higher RCADS-P scores than children without an internalizing diagnosis. Finally, the RCADS-P had good-to-excellent diagnostic efficiency, and a total sum score of 25 had excellent sensitivity and fair specificity. Findings provide psychometric support for the RCADS-P in children with ADHD.